(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below: A 10-year old boy, the only issue of his deceased parents, was admitted to the department for the management of recurrent episodes of diarrhea and severe wasting for 2.5 months, low grade, irregular fever with evening rise of temperature, anorexia and repeated attack of skin blister for the last 1 year. The patient complained of chronic, painless, non-bloody, profuse watery diarrhea with a weight loss of 10 kg (decrease to 18 kg from 28 kg prior to illness). He also complained of cough for the last seven days. His father was a driver and died at his 1 year of age due to an unknown disease.